Práticas de TIC verde como suporte para o desenvolvimento sustentável - Indi, Joel Amaque da Silva (2016)
The Information and Communication Technology (ICT) is getting more and more space, whether in industry, commerce or even for personal use, offering support to other areas in the acquisition of knowledge, providing greater agility in the execution of innovative processes. However, the incorrect or uncontrolled use of ICT resources and equipment, can lead to several negative consequences, for explample e-waste, which through its chemical compounds cause pollution to the environment, causing harm to human health. For this reason, it came to Green ICT, which are sustainable management practices in order to reduce quantities of non-renewable raw materials in the production of ICT equipment, as well as unnecessary waste of raw materials, save energy and minimize the use of substances toxic in the manufacture of such equipment. Green ICT is proposing methods for use and manufacture of ICT equipment in accordance with ecological principles. Ie, combining the ICT resources available to sustainability policies and economy within organizations, generating benefits for the environment and for business. Therefore, this study demonstrated based on the literature the reduction of CO2 (carbon dioxide) that the ICT industry can provide up to 2020. As well, assessed the adoption of Green ICT in the state of Ceará, Brazil, parts of companies specialized in ICT and non-specialized, but have embedded ICT sector, and thus identify components that influence environmental sustainability in the ICT area. To this end, we conducted a case study involving 55 multiple segment companies, randomly selected and are located in different regions of the state of Ceará. The research was mainly qualitative, the main source of data collection the questionnaire, with subsequent analysis of the implications. As a result, it was confirmed that the total of the specialized cearense companies in ICT, 30% did not know Green ICT and its use, and this ignorance is even greater for companies not specialized in ICT, totaled 64%. Only 18% of these, exercise sustainable practices of ICT, because for 29% of them is not a priority of the company concerned with sustainable practices of ICT. On the other hand, 50% of companies specializing in ICT who do not exercise sustainable practices, not to do so because they need advice on the subject. So moved by these results, a green ICT implementation guide has been produced to guide companies that make use of information and communication technology to adhere to sustainable practices.